Authorship in Mozambique: the case of António Quadros - Stennett, T (2020)
In this thesis, I examine the question of authorship in late-colonial and post-independence Mozambique through the case of the eccentric figure of Portuguese artist and writer António Quadros (1933-1984), who wrote and published most of his works in Mozambique. The study draws on archival research, interviews with associates and colleagues of Quadros, close textual analysis and postcolonial and critical theory. It is the first substantial study on the problematic of authorship in Mozambique and on the understudied writer António Quadros.